Transparent Antenna for Green Communication Feature: A Systematic Review on Taxonomy Analysis, Open Challenges, Motivations, Future Directions and Recommendations - Alobaidi O.R.; Chelvanathan P.; Tiong S.K.; Bais B.; Uzzaman M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antenna applications; Best practices; Green communications; Inclusion and exclusions; Multiple platforms; Renewable energies; Systematic Review; Web of Science; Antennas